The analysis of endothelial nitric oxide synthase gene polymorphism in intron 4 with hypertension disease - Zarmakhi, Leila; Hashemi, Mehrdad (Archives of Advances in Biosciences, 2012)
Nitric oxide is an important vasorelaxant factor that it inhibits platelet adhesion and proliferation of smooth muscle cells. NO is synthesized from L-arginine by means of endothelial nitric oxide synthase (eNOS) which is an isoform of Nitric Oxide Synthase.In the present study, we examined possible association between the 27 base pair (bp) repeat polymorphism in intron 4 of the eNOS3 gene and hypertension in an Iranian population. 40 patients with hypertension and 40 healthy controls were included in the research.Genotyping was performed by polymorphism chain reaction (PCR). The frequency of 4a4a, 4a4b , 4b4b genotypes were 52.6% , 26.3%, 15.7% respectively in hypertension groups .The frequency of 4a4a, 4a4b , 4b4b genotypes were 73.8% , 15.7% , 10.5% respectively in control groups. The hypertensive patient group showed a significant higher frequency of the 4a allele compared to the controls (p<0.01).The present study showed a singificant association between the eNOS3 gene polymorphism and hypertension in the Iranian population .